Immunogenicity of the UK group B meningococcal vaccine (4CMenB) schedule against groups B and C meningococcal strains (Sched3): outcomes of a multicentre, open-label, randomised controlled trial. Issue 5 (May 2021) - Davis, Kimberly; Valente Pinto, Marta; Andrews, Nick J; Goldblatt, David; Borrow, Ray; Findlow, Helen; Southern, Jo; Partington, Jo; Plested, Emma; Patel, Sima; Holland, Ann; Matheson, Mary; et al.
Summary: Background: The use of the multicomponent meningococcal vaccine 4CMenB in the UK schedule at 2, 4, and 12 months of age has been shown to be 59·1% effective at preventing invasive group B meningococcal disease. Here, we report the first data on the immunogenicity of this reduced-dose schedule to help to interpret this effectiveness estimate. Methods: In this multicentre, parallel-group, open-label, randomised clinical trial, infants aged up to 13 weeks due to receive their primary immunisations were recruited via child health database mailouts in Oxfordshire and via general practice surgeries in Gloucestershire and Hertfordshire. Infants were randomly assigned (1:1) with permuted block randomisation to receive a 2 + 1 (2, 4, and 12 months; group 1) or 1 + 1 (3 and 12 months; group 2) schedule of the 13-valent pneumococcal conjugate vaccine (PCV13). All infants also received 4CMenB at 2, 4, and 12 months of age, and had blood samples taken at 5 and 13 months. Participants and clinical trial staff were not masked to treatment allocation. Proportions of participants with human complement serum bactericidal antibody (hSBA) titres of at least 4 were determined for group B meningococcus (MenB) reference strains 5/99 (Neisserial Adhesin A [NadA]), NZ98/254 (porin A), and 44/76-SL (factor H binding protein [fHbp]). Geometric mean titres (GMTs) with 95% CIs were also calculated, and concomitant vaccine responses (group C meningococcus [MenC], Haemophilus influenzae b [Hib], tetanus, diphtheria, and pertussis) were compared between groups. The primary outcome was PCV13 immunogenicity, with 4CMenB immunogenicity and reactogenicity as secondary outcomes. All individuals by randomised group with a laboratory result were included in the analysis. The study is registered on the EudraCT clinical trials database, 2015-000817-32, and ClinicalTrials.gov, NCT02482636, and is complete. Findings: Between Sept 22, 2015, and Nov 1, 2017, of 376 infants screened, 213 were enrolled (106 in group 1 and 107 in group 2). 204 samples post-primary immunisation and 180 post-boost were available for analysis. The proportion of participants with hSBA of at least 4 was similar in the two study groups. For strain 5/99, all participants developed hSBA titres above 4 in both groups and at both timepoints. For strain 44/76-SL, these proportions were 95·3% (95% CI 88·5–98·7) or above post-priming (82 of 86 participants in group 1), and 92·4% (84·2–97·2) or above post-boost (73 of 79 participants in group 1). For strain NZ98/254, these proportions were 86·5% (78·0–92·6) or above post-priming (83 of 96 participants in group 2) and 88·6% (79·5–94·7) or above post-boost (70 of 79 participants in group 1). The MenC rabbit complement serum bactericidal antibody (rSBA) titre in group 1 was significantly higher than in group 2 (888·3 vs 540·4; p=0·025). There was no significant difference in geometric mean concentrations between groups 1 and 2 for diphtheria, tetanus, Hib, and pertussis post-boost. A very small number of children did not have a protective response against 44/76-SL and NZ98/254. Local and systemic reactions were similar between the two groups, apart from the 3 month timepoint when one group received an extra dose of PCV13 and recorded more systemic reactions. Interpretation: These data support the recent change to the licensed European schedule for 4CMenB to add an infant 2 + 1 schedule, as used in the routine UK vaccine programme with an effectiveness of 59·1%. When compared with historical data, our data do not suggest that effectiveness would be higher with a 3 + 1 schedule, however a suboptimal boost response for bactericidal antibodies against vaccine antigen fHbp suggests a need for ongoing surveillance for vaccine breakthroughs due to fHbp-matched strains. Changing from a 2 + 1 to a 1 + 1 schedule for PCV13 for the UK is unlikely to affect protection against diphtheria, tetanus, and Hib, however an unexpected reduction in bactericidal antibodies against MenC seen with the new schedule suggests that ongoing surveillance for re-emergent MenC disease is important. Funding: Bill & Melinda Gates Foundation and the National Institute for Health Research.